Is near infrared spectroscopy valid for the detection of procedural pain in postoperative cardiac surgery intensive care unit adults?. Issue 6 (December 2017) - Gélinas, Céline; Boitor, Madalina; Ranger, Manon; Johnston, Celeste C; de Marchie, Michel; Cervero, Fernando; Choinière, Manon
This study aimed to examine the validity of the regional cerebral oxygenation using the near infrared spectroscopy technique for pain assessment in postoperative cardiac surgery adults in the intensive care unit. The near infrared spectroscopy for the assessment of pain has been studied in pediatric population, but its use in adult population especially in the critically ill is new. A total of 125 cardiac surgery intensive care unit patients from a Canadian university-affiliated hospital participated in this prospective repeated-measures study. Six assessments were completed at rest before, during, and 15 min after two procedures: (1) non-nociceptive (blood pressure measurement using cuff inflation) and (2) nociceptive (mediastinal tube removal). Regional cerebral oxygenation (%) was measured using the INVOS 5100 device (Somanetics, Troy, MI, USA). The Critical-Care Pain Observation Tool was employed to assess behavioral responses to pain. Self-reports of pain intensity and unpleasantness using 0–10 scales were also obtained. Participants were mostly males (89%) and averaged 65 of age. Regional cerebral oxygenation showed significant mild bilateral decreases (<1%; p <0.01) while higher mean Critical-Care Pain Observation Tool scores, pain intensity, and unpleasantness self-reports were obtained during mediastinal tube removal ( p < 0.001). Only the Critical-Care Pain Observation Tool score was mildly correlated to the right side regional cerebral oxygenation ( r −0.23; p < 0.01). Changes in regional cerebral oxygenation were mild and in the opposite direction. Unfortunately, the findings do not support the clinical use of the INVOS 5100 (Somanetics, Troy, MI, USA) and its regional cerebral oxygenation hemodynamic parameter for the assessment of pain in the cardiac surgery critically ill patients.